Navigating Complex, Ethical Problems in Professional Life: a Guide to Teaching SMART Strategies for Decision-Making - McIntosh, Tristan (J Acad Ethics, 2020)
This article demonstrates how instructors of professionalism and ethics training programs can integrate a professional decision-making tool in training curricula. This tool can help trainees understand how to apply professional decision-making strategies to address the threats posed by a variety of psychological and environmental factors when they are faced with complex professional and ethical situations. We begin by highlighting key decision-making frameworks and discussing factors that may undermine the use of professional decision-making strategies. Then, drawing upon findings from past research, we present the “SMART” professional decision-making framework: seeking help, managing emotions, anticipating consequences, recognizing rules and context, and testing assumptions and motives. Next, we present a vignette that poses a complex ethical and professional challenge and illustrate how each professional decision-making strategy could or should be used by characters in the case. To conclude, we review a series of educational practices and pedagogical tools intended to help trainers facilitate trainee learning, retention, and application of “SMART” decision-making strategies.